2007
DOI: 10.1038/sj.ki.5002427
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic retroperitoneal fibrosis: Clinicopathologic features and differential diagnosis

Abstract: Idiopathic retroperitoneal fibrosis (IRF) is a rare disease often causing obstructive uropathy. We evaluated the clinicopathologic features of 24 patients with IRF to characterize the histopathology of the disease and to provide a framework for the differential diagnosis with other retroperitoneal fibrosing conditions. Retroperitoneal specimens were analyzed by light and electron microscopy and by immunohistochemistry. Most patients presented with abdominal/lumbar pain, constitutional symptoms, and high acute-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 58 publications
10
121
3
7
Order By: Relevance
“…The male-to-female ratio was 1:0.6 in our series, which is similar to that previously reported (1:0.3-1:0.8 (11)(12)(13)(14)). In one review of 14 cases of IgG4-related RF (23), all patients were men and their mean age was 67 years.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The male-to-female ratio was 1:0.6 in our series, which is similar to that previously reported (1:0.3-1:0.8 (11)(12)(13)(14)). In one review of 14 cases of IgG4-related RF (23), all patients were men and their mean age was 67 years.…”
Section: Discussionsupporting
confidence: 81%
“…The mean age at diagnosis of IgG4-related RF was 70.1 years in our series, whereas previous studies have reported a younger mean age at diagnosis, ranging from 54.2 to 64 years (11)(12)(13)(14). The male-to-female ratio was 1:0.6 in our series, which is similar to that previously reported (1:0.3-1:0.8 (11)(12)(13)(14)).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…There Picture story are idiopathic (as in our patient) and secondary forms. Renal failure due ureteric obstruction is common [3]. Only very few reports of kidney transplantation in such patients.…”
Section: Discussionmentioning
confidence: 99%